Feeding behaviour of autumn passage migrants in north east Portugal - Ferns, Peter N. (Ringing & Migration, 1975)
IN THE SUMMER and autumn of 1973, a mist netting site in the sparsely wooded hill country of north east Portugal was continuously manned by members of the Iberian Ringing Group. The main objective was to study the increases in weight of trans-Saharan passerine migrants which use this particular area as a staging post on their southward journey (Mead 1968). These migrants arrive on the central Iberian plateau towards the end of a long, dry summer, at a time when conditions appear relatively inhospitable. Yet Willow Warblers* and Pied Flycatchers gain over 0.2 g/day in weight, while Whitethroats increase by over 0.4 g/day (C. J. Mead and B. R. Watmough in prep.). Though this is somewhat less than, for example, the 0.6 g/day gained by Whitethroats at Lake Chad, Nigeria, in preparation for the return journey to the Palaearctic in spring (Fry. Ash and FergusonLees 1970), it still suggests that reasonable food supplies are available. In order to determine the nature of the foods being taken by these migrants, a series of observations were made during late August and early September 1973 in association with mist-netting activities.
doi: 10.1080/03078698.1975.9673692doi: 10.1080/03078698.1975.9673692The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Feeding activity; Feeding habits (PG); migration; passerines